Moving Pictures: Animation and Revision in Loving Vincent - Jellenik, Glenn (Transcr(é)ation)

(untitled) (Western Libraries, University of Western Ontario, 2025)
Loving Vincent (2017) functions as an adaptation in several interesting ways: narratively, the animated feature is a biopic that adapts Vincent van Gogh’s life, specifically the weeks leading up to his death. Visually, the film adapts the artist’s style through animation, employing van Gogh’s techniques, characters, and settings in order to flesh out and revise the events of his last days.From the perspective of adaptation theory, Loving Vincent enacts a productive series of engagements with fidelity. This essay argues that the animation’s hyper-faithful mimicking of van Gogh’s aesthetics paves the way for its revisionist version of his death, one which departs significantly from previous historical accounts. These constructive plays with fidelity—remaining hyper-faithful to the artist’s style and aesthetics while simultaneously challenging plot-points of his death—rehearse the full and complex spectrum of fidelity in adaptation. Whether we, as critics, like it or not, concepts of fidelity (and the audience-expectations they enact) are issues confronted and engaged by every adaptation.An engagement with the animated and narrative aspects of Loving Vincent suggests that rather than being prescriptive, concepts of fidelity can create a productive tension in an adaptation. The film’s animation constructs a visual fidelity that enables a free play with historical speculation that might otherwise jar viewers. Ironically, the film’s use of animation (meticulously reproducing van Gogh’s style) lends the text a level of realism and authority that smooths the genre play (the biopic is delivered in the form of a detective story) and revisionist history (adapted from the 2011 biography Van Gogh: The Life). In this way, we might see Loving Vincent’s animation as simultaneously establishing continuity and providing expansion and elaboration, to borrow terms from transmedia studies.